2017
DOI: 10.1016/j.psychsport.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

“I don't know if I would report them”: Student-athletes' thoughts, feelings and anticipated behaviours on blowing the whistle on doping in sport

Abstract: The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we will investigate on a case-by-case basis. Each thesis in the repository has been cleared where necessary by the author for third party copyright. If you would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
5
26
1
Order By: Relevance
“…Stepanov regarding Russian Athletics), the concept of reporting wrongdoing has garnered increasing interest from researchers (Erickson, Backhouse, & Carless, 2017;Whitaker, Backhouse, & Long, 2014), the media and anti-doping organisations worldwide. Despite the increased emphasis and reliance upon intelligence-driven deterrence over the traditional detection-deterrence approach (i.e., drug testing), research on doping whistleblowing has not kept pace with the developments in anti-doping policy and practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stepanov regarding Russian Athletics), the concept of reporting wrongdoing has garnered increasing interest from researchers (Erickson, Backhouse, & Carless, 2017;Whitaker, Backhouse, & Long, 2014), the media and anti-doping organisations worldwide. Despite the increased emphasis and reliance upon intelligence-driven deterrence over the traditional detection-deterrence approach (i.e., drug testing), research on doping whistleblowing has not kept pace with the developments in anti-doping policy and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increased emphasis and reliance upon intelligence-driven deterrence over the traditional detection-deterrence approach (i.e., drug testing), research on doping whistleblowing has not kept pace with the developments in anti-doping policy and practice. Few researchers have considered the issue (see Whitaker et al, 2014;Erickson et al, 2017), and insights from individuals who have actually blown the whistle on doping are unavailable. This lack of understanding, alongside growing recognition for the limitations to the detection-deterrence approach (e.g., drug tests will never be able to detect all substances) inspired the present research.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings highlight the role of sportspecific norms and expectations around reporting doping misconduct (Whitaker et al, 2014). Another study (Erickson et al, 2017) also found that student athletes were reluctant to report ADRVs to a third party. Instead, they would prefer to personally confront athletes who commit ADRVs as a way to de-normalize doping in sport.…”
mentioning
confidence: 76%
“…Whistleblowing against ADRVs and other doping-related misconduct has been recognized as an effective deterrent of doping behaviour in sport (Erickson et al, 2019;Verschuuren, 20202020), and WADA has invested significant resources in promoting this behaviour among competitive and elite athletes. Nevertheless, research on this topic is scarce and largely exploratory, using qualitative/inductive methods and small samples of athletes and students (e.g., Erickson et al, 2017;Whitaker et al, 2014). The present study is the first one to empirically assess whistleblowing intentions against doping misconduct using: (a) quantitative research methods and multivariate statistical analyses, (b) a specific theoretical framework, and (c) a large international sample of competitive, highperforming athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The revised WADC (Article 10.6.1) supports the provision by athletes of substantial assistance to uncover anti-doping rule violations by offering the possibility of reducing the length of their sanctions reduced or even completely remove them ( World Anti-Doping Agency [WADA], 2015a ). Up until now there have been some studies with a focus on athletes’ perception of reporting doping or whistleblowing ( Whitaker et al, 2014 ; Erickson et al, 2017 ), but none take account of a leniency program.…”
Section: Anti-doping Policy and Its Backgroundmentioning
confidence: 99%